Hisbah operations, public morality and social justice : a case study of Kano state, Nigeria - Hizqil, Habib Muhammad (Kulliyyah of Islamic Revealed Knowledge & Human Sciences, International Islamic University Malaysia, 2014)
The Sharī'ah reintroduction in 12 out of the 19 Northern States of Nigeria raised the demand for an institution that will be responsible for the Sharī'ah implementation, as well as speedy societal reorientation in the affected states including Kano. The task of Ḥisbah institution in Sharī'ah implementation is enormous considering long years spent under a secular political system that derives its laws from the constitution, which is also secular in nature. Therefore, with the present system being in action, Sharīᶜah implementation falls outside the jurisdiction of the Nigeria Police Force as they operate under the Police Act. Consequently, Ḥisbah institution was established in Kano and since its inception, efforts have been geared towards implementing Sharīᶜah within its jurisdiction. In the course of discharging its noble functions, the institution faces many challenges and resistance from a segment of the public and security agencies, who seem to have a negative perception about Ḥisbah operations. Therefore, the objective of the study is to evaluate the performance of the Kano State Ḥisbah Board in the restoration of public morality and ensuring social justice among the deviants, as reformation and rehabilitation is one of the cardinal objectives of Sharīᶜah. The study used mixed methods (quantitative and qualitative) in generating data from multiple sources in the research process, which involved 700 samples drawn from the public that comprises of married couples, widows and divorces, independent women and commercial motorcycle riders, as well as the Ḥisbah personnel. Questionnaire instrument was administered to these samples, while qualitative data was generated through interview with experts that include: the former Commander-General of the Ḥisbah Board; former Deputy Commander-General (Operations) and the former Deputy Commander-General (Women Wing); as well as the Chairperson of the Amalgamated Motorcycles Owners and Riders Associations of Nigeria (ACOMORAN) Kano State Chapter. This helped in supplementing the data generated from the questionnaire. Statistical Package for Social Sciences (SPSS) version 20.0 was employed in processing and managing the data in the study. Descriptive statistics (frequency and percentage) and independent t-test were used to answer the questions and the hypotheses regarding public perception on Ḥisbah, influence of Ḥisbah operations on public morality and social justice, determining the relationship between Ḥisbah and other security agencies, as well as the operational challenges facing Ḥisbah in the course of performing its duties. The findings of the study indicate that the public has a positive perception on Ḥisbah, as well as its operations in the areas of public morality and social justice and no significant differences between genders were found in all the dimensions. Similarly, the findings show that there is a cordial relationship between Ḥisbah and the conventional security agencies in the state, despite resistance from a segment of the society.